Antagonistic Study of Lantana camara (Linn) against with Pathogenic Bacteria - Vaidya, Geeta Shrestha; Bhattarai, Nabin (Scientific World, 2010)
A research work of antagonistic effect of water solvent and organic solvent (Ethanol of different concentration 50 % and 100 %) of extracts of Lantana camara were studied against with pathogenic fifteen strains of bacteria. Among fifteen species, of bacteria most of them were inhibited by L.camara extracts and only two species such as Klebsella oxytoca and Klebsella pneumoniae did not showed antibacterial activity with same extract with same concentration. Extracts obtained from the organic solvent and water solvent showed the different antagonistic properties with the same bacterial strains. Those bacterial strains which were inhibited their growth by water solvent could not inhibited by organic solvent extracts. This depends on presence of polar and non-polar bioactive compounds in the extracts. It also depends on polar and non-polar solvents used for the plant extract. Organic solvent extracts showed antibacterial effect towards Pseudomonas aeruginosa, Staphylococcus sp., Bacillus cereus, Bacillus subtilis, Bacillus thurengiensis, Escherichia coli, Staphylococcus aureus, Proteus mirabilis and water solvent extracts showed antibacterial effect towards Pseudomonas aeruginosa, Staphylococcus sp., Citrobacter frundi, Proteus sp., Bacillus subtilis, Enterobacter aerogenes, Salmonella paratyphie, Staphylococcus aureus, Shigella dysenteria. Both solvent extracts showed high antibacterial effect towards Staph aureus, Staphylococcus sp. and Pseudomonas aeruginosa. Both plant extracts showed selective antibacterial effect with different strains of bacteria, which shows that these are confined to cure the same bacterial diseases. Key words: Lantana camara; Pathogenic bacteria; Antimicrobial; Organic and water solvent; Concentration. DOI: 10.3126/sw.v7i7.3828 Scientific World Vol.7(7) 2009 pp.64-67